Analysis of the Presentation Techniques of Bangkok’s History in the Bangkok Knowledge: Old Quarter Stories Book for Learners of Thai as a Foreign Language - ZENG, XUEYUAN; Pornumpaisakul, Nition (Academic and Research Journal of Liberal Arts (Online), 2025)
This article analyzes the presentation techniques used to depict the history of Bangkok in the book Bangkok Knowledge: Old Quarter Stories for learners of Thai as a foreign language. The study found that the book employs key ten presentation techniques: (1) use of illustrations, including photographs, drawings, and maps; (2) explanatory methods, including explaining with short texts and explaining with examples; (3) question-and-answer methods, including using questions as headings and embedding questions within the content; (4) character creation; (5) chronological storytelling; (6) insertion of interesting facts; (7) use of dialogue; (8) comparative techniques; (9) diverse source referencing; and (10) use of idioms. These techniques help present the complex and multifaceted history of Bangkok in an engaging and comprehensible manner. However, these techniques make the content more accessible and easier to understand. They not only facilitate understanding but also capture learners’ interest, making the book suitable for studying history, society, and culture within the context of learning Thai as a foreign language, these methods contribute to more effective Thai language learning.